Konsep Pendidikan Karakter Menurut Prof. Dr. H. E. Mulyasa, M.Pd - Novan Ardy Wiyani (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: This paer is intened to find the concept of character education, according to Prof. Dr. H. E. Mulyasa thas various books he wrote. Hopefully, this article can serve as guidelines for the parties the manager (manager) schools in practing character education within the scope of the school. From the result of the study can be obtained information that character education is agrowing process of character values, such as conscious, honest, sincere simple, independent, caring, free to act however responsible for his action, careful or conscientious, and commited to doing good. Internalization of character values us carried out through three strategies, namely be a good example for their students, internalize the character values into learning activities, internalize the character values into the activities of habituation, and then manage the school in favor of the practice providing education character. Keywords character, values, strategies, exemplary